The Planning Development of Tourism - Regulation or Deregulation? - Bosiacki, Stefan; Panasiuk, Aleksander (Studia Oeconomica Posnaniensia, 2017)
The scope of the study includes theoretical issues relating to tourism policy, together with an indication of the dynamics of the changes in the global tourism market. A diagnosis will be presented of the current tourism policy in Poland, together with an assessment of the effectiveness of system solutions and planning instruments. The background discussion will be the European Union policy in the field of tourism and issues of financing the development of tourism from EU funds in the financial perspectives of 2007-2013 and 2014-2020. On the basis of the diagnosis proposals will be outlined for changes in the Polish model of tourism policy in the context of solutions in the European Union. In addition, local and regional authorities will be indicated in the proposed model. The aim of the paper is to assess the current model of tourism policy in Poland against the background of global solutions and the European Union together with proposed solutions in the field of tourism policy in the medium and long term. The scope of the methods used include: literature studies, logic operations, comparative analysis, and heuristic methods. The test period covers the years 2007-2014 ex post and the proposals will concern the horizon 2022. Issues of socio-economic policy are conceptual. The test results can be used for shaping tourism policy in Poland by competent bodies: central, regional and local. The diagnosis of tourism policy, together with proposals for it to be changed is the personal opinion of the authors. In this form of consideration, they have not been presented in the literature sources.